Genetic associations of docetaxel‐based chemotherapy‐induced myelosuppression in Chinese Han population. (28th November 2019) - Ren, Weihua; Zhou, Chenxi; Liu, Yedong; Su, Keli; Jia, Li; Chen, Luan; Li, Mo; Ma, Jingsong; Zhou, Wei; Zhang, Suli; Zhang, Di; Cong, Zhiliang; et al.
Abstract: What is known and objective: Myelosuppression, an adverse drug reaction (ADR), often causes medical treatment termination in cancer patients. It has been known that genetic components, such as single‐nucleotide polymorphisms (SNPs), influence the risk of myelosuppression at the individual‐patient level. However, due to ethnic variation in frequency of genetic polymorphisms, results reported in Caucasian patients may not be generalizable to the Chinese Han population. Until now, few researches on myelosuppression included Chinese Han patients. In this study, we conducted a systematic study of potential biomarkers for docetaxel‐induced myelosuppression in Han Chinese patients. Methods: We examined 61 SNPs in 36 genes that code for drug transporters, metabolism enzymes, nuclear receptors and DNA repair pathway in 110 Chinese Han patients receiving docetaxel‐based chemotherapy. Genotyping was conducted using the Sequenom MassARRAY system. Significant SNPs were identified by logistic regression, and gene‐gene interactions were investigated by generalized multifactor dimensionality reduction (GMDR) analysis. Results and discussion: Our results revealed that 11 SNPs in nine genes ( SLC15A1, SLCO1A2, CYP2D6, FMO3, UGT1A1, NAT2, SULT2A1, PXR and HNF4α ) were associated with docetaxel‐induced myelosuppression. GMDR analyses suggested that a 3‐locus model: SLC15A1 rs2297322— PXR rs3732359— FMO3 rs2266782 was an appropriate predictive model of docetaxel‐induced myelosuppression ( P  = .017, Testing Bal.Acc = 0.653, CV Consistency = 10/10). What is new and conclusion: Our findings suggest multiple novel predictive biomarkers of docetaxel‐induced myelosuppression: SLC15A1 rs2297322, PXR rs3732359 and FMO3 rs2266782. These discoveries should help in advancing future personalized therapy of docetaxel‐based chemotherapy specific to Chinese Han patients. Abstract : Gene‐gene interaction models